Study on the correlation between sleep disorders and the progression of periodontitis - WU Chengyu, YE Yu, XUE Chang'ao (Editorial Office of Stomatology, 2024)
Objective To conduct a cross-sectional study on sleep and periodontal conditions, and further analyze the correlation between sleep disorders and the progression of periodontitis. Methods A total of 100 patients who visited the Department of Stomatology at Nanjing First Hospital from June 2022 to October 2023 and met the inclusion criteria were selected. According to the 2018 International New Classification of Periodontitis and Implant Periodontitis, patients were divided into stages Ⅰ-Ⅳ of periodontitis. General patient information was recorded. A Pittsburgh sleep quality index (PSQI) questionnaire survey was conducted to understand the patient's sleep status, and routine periodontal examinations were conducted to record probing depth (PD), periodontal attachment level (AL), bleeding index (BI), and blood routine tests were used to measure white blood cell count. The correlation between sleep disorders and periodontitis was statistically analyzed. Results The average PSQI score of all patients was (7.01±3.17) points, with an average PD of (3.52±0.67) mm, an average AL of (3.84±1.58) mm, and an average BI of (3.15±1.26). Among them, patients with stage Ⅳ periodontitis had the highest PSQI score. The white blood cell count of patients with stage Ⅲ and Ⅳ periodontitis was higher than that of patients with stage Ⅰ and Ⅱ (P<0.05), and the white blood cell count of patients with sleep disorders and periodontitis was higher than that of patients with periodontitis without sleep disorders (P<0.000 1). Using PSQI score as the independent variable and periodontitis stage as the dependent variable, after adjusting for age, gender, smoking, brushing frequency, and white blood cell count, regression analysis showed an OR of 1.480 2 (95% CI: 1.248 5-1.755 0). Conclusion There is a correlation between sleep disorders and periodontitis, and sleep disorders can promote the occurrence and development of periodontal tissue inflammation.